Gaze interaction and applications of eye tracking : advances in assistive technologies - Majaranta, Paivi, 1967- (Hershey, PA : Medical Information Science Reference, 2012)
'This book focuses on interactive communication and control tools based on gaze tracking, including eye typing, computer control, and gaming, with special attention to assistive technologies'--
'Premier Reference Source'--Cover.
Includes bibliographical references and index.
Keywords: Eye tracking; Human-computer interaction; Self-help devices for people with disabilities; Computerized instruments; Eye -- Movement -- Photographic measurements